Ultra-precision grinding of piezoelectric ceramic thick films for fabrication of pre-stressed bimorph microactuators and development of new numerical models to assess induced thermal stress in multilayer structure - Jourdain, R. P. (Cranfield University, 2005)
The research programme aims to develop a novel 2.5 dimensional fabrication process for multilayer piezoelectric microactuators. Ultra-precision grinding was used in conjunction with standard micro-fabrication techniques and adhesive bonding technology to create a powerful bimorph structure. The multilayer structure forms the heart of a microvalve device and it comprises piezoelectric ceramic layers joined to a metal shim at relatively low temperature (200° Celsius). I contrast with existing thick deposition techniques this new fabrication technique does not adversely affect the electro-active properties of the ceramic material and it has the further advantage that it is not substrate sensitive making it compatible with the wide range of materials available for micro-scale device construction. The objectives of this project were twofold: > To investigate the mechanism of the material removal process for piezoelectric ceramics using a ultra-precision grinding machine tool on four different piezoelectric materials. The research work investigated both planarization and surface integrity. > To develop different models using the definite element analysis technique to analyse and assess the thermally induced stress due to the bonding process. Direct and initial stress loading conditions were analysed and applied to a multilayer structure. This work ends with a fully characterized symmetric structure for bimorph cantilevers. Grinding is shown to be a suitable machining technique to prepare the surface of piezoelectric ceramic discs. The required surface quality is fully achieved for the target microsystems application. Surface flatness and roughness have been scientifically investigated through a experimental plan. The infinite element analysis reveals some valuable results relating to stress intensity and explores the effect of changes due to thermal expansion coefficient mismatch and the influence of adhesive bond thickness in a multilayer structure. Use of initial stress loading allows simulation of complex processes of fabrication leading to optimization of the structure. h this way a improved fabrication process has been established which avoids any profile deformation. Finally the performance of the bimorph cantilevers is predicted through analytical and numerical modelling and a correlation is established.